Microbiological Quality Assessment of Foods collected from Different Hospitals within Dhaka City (Stamford Journal of Microbiology, 2011)
Various types of cooked food samples were collected from six different hospitals within the city of Dhaka and they were analyzed for the presence (if any) of total aerobic count (TAC), total coliform count (TCC) and total staphylococcal count (TSA) in order to determine the levels of contamination and to relate these findings to the hygiene practice of the food handlers. According to Gulf standard for microbiological criteria for foodstuff, all of the food samples exceeded the acceptable total aerobic count limit of 5 x 105 cfu/g while 4 out of 6 samples exceeded coliform count limit of 1x102 cfu/g. The total coliform counts were found to be the highest in the fish (1.6 x 107 cfu/g) and egg (2.2 x 106 cfu/g) curry samples of hospital 1 and hospital 4, respectively and were the lowest in the fish curry (2 x 103 cfu/g) of hospital 4. Staphylococcus aureus was found in all of the food samples with the highest occurrence (too numerous to count) in Dal and Rice samples from hospitals 3 and 6, respectively. On Xylose Lysine Deoxycholate (XLD) agar, no black centered colony but many colorless colonies were found which primarily indicated the absence of Salmonella spp. in those samples. In order to identify pathogenic microorganisms from food samples, a series of conventional biochemical tests were performed with 23 randomly selected isolates from MacConkey, XLD, MSA agar plates. The isolates were presumptively identified as Escherichia coli, Staphylococcus aureus, Shigella spp. and Pseudomonas spp. etc. The antibiotic susceptibility test was performed with eleven selected isolates using six commonly prescribed antibiotics (ampicillin, tetracyclines, ciprofloxacin, vancomycin, gentamicin and azithromycin). The results showed that six isolates were resistant to vancomycin, two isolates were multidrug resistant and one isolate was intermediately resistant to azithromycin. All the isolates were found to be sensitive to ciprofloxacin, and gentamicin. Based on the data, it can be suggested that adequate hygiene practices are required after cooking the foods and before serving them as they reconsider.DOI: http://dx.doi.org/10.3329/sjm.v1i1.9100  Stamford Journal of Microbiology, Vol.1(1), July 2011, p.31-36